Changes in the ovary and the peripheral concentrations of sex hormones after the aspiration of follicular fluid from the spontaneous follicular cysts of dairy cows - Kazuhiro KENGAKU; Tomomi TANAKA; Hideo KAMOMAE (The Society for Reproduction and Development, 2021)
The aim of the present study was to clarify the ovarian and hormonal dynamics after the aspiration of follicular fluid in cows with follicular cysts. Follicular fluid was aspirated from the follicular cysts and follicles that were fated to become cystic follicles and other coexisting normal follicles, respectively, in lactating cows (n = 3). After the aspiration procedure, new follicles developed and reached a diameter of 25 mm without ovulation within 13-19 days. The plasma concentrations of inhibin decreased and follicle-stimulating hormone increased rapidly after the aspiration procedure, and subsequently increased and decreased, respectively, as a new follicle grew. No luteal structures developed after the aspiration procedure, and the animals' plasma progesterone levels remained low. The present study indicates that the cystic follicles are never luteinized by the aspiration of follicular fluid, and consequently, new follicular cysts are observed to repeatedly develop.